Research on secure DPC localization algorithm of WSN - ZHAN Jie1; LIU Hong-li1; LIU Da-wei1; ZHAO Ming3 (Tongxin xuebao)
In resource-constrained sensor networks,how to locate the sensor’s coordinates securely and effectively is one of the most challenging problems.A lot of algorithms of the security localization were analyzed,and a distributed RSSI-based DPC（distance and position consistent） security location algorithm was brought forth.The algorithm can de-tect and filter out the false nodes that are generated by malicious attacks applying the consistency of measure and com-puting;meanwhile all the nodes are involved in the activation without a central node.The performance of the algorithm is studied,and the experimental results show that DPC still has very high efficiency and good robustness in noisy conditions with a number of false nodes.